(3eYjf GdMcGe aj eG jJQOO Hjf GdNUejf ef GdCMcGes - (3Ydj Hf Ndjd GdWQGHdSj, CHh GdMSf, YdGA GdOjf,J (B844 (3g` s ((3eMeO Hf RcQjG s)
(3ChdgG (B:s
(3JHGQc GdPi CHOY GdehLhOGJ HbOQJg CMeOg Ydi eG hgH hde Cba Ydi JCdja CZfi ajg HGdESJjYGH GdcTa Yf ZhGeV gPG Gdaf (B_ (3jQjO GdbVGA (B_ (3aQCjJ fXe egeGJg ai Sdc hGMO hSejJg hQJHJg Ydi KdGKI CbSGe s
(3BNQgG (B:s
(3gPG JeGe GdcJGH hdbO hajJ ajg HVHW GdbhGYO GdcdjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3eDWQI HGdMeQI s
(3cJHJ GdYfGhjjf HGdMeQI s
(3Ydi WQJgG Jedc eDQN SfI (B1282 (3g` HGSe GdMGL eMeO SdWGf s
Keywords: (3Gdabg GdMfajs